Islamic Law Versus Adat: Debate about Inheritance Law and the Rise of Capitalism in Minangkabau - Yasrul Huda (Studia Islamika, 2008)
The study of traditional Minangkabau society has stimulated a considerable amount of work on the nature of social change in West Sumatra. In Minangkabau one of the central themes of its intellectual history is the search for the formulation of the relationship between adat and Islam. As a result, some scholarly debated has concentrated on how a matrilineal society, such as Minangkabau, can become one of the most thoroughly Islamized ethnic groups. The survival of adat is under the domination of Islam, although its rules are extremely different from adat, and the integration of Islam with adat.DOI: 10.15408/sdi.v15i2.531